Produksi Video Klip Multiplek Lagu â€œSemalam di Cianjurâ€ Berbasis Multimedia - Hendraningrat, R Wahyu; Hepy Urbani, Yunanto (Speed - Sentra Penelitian Engineering dan Edukasi, 2014)
Abstract :Â  Multiplex is a special type of karaoke songs that have the ultimate guide vocal, which helps to learn the track. Vocals were recorded on only one side of the stereo channels, making it possible to be processed with Sony Vegas software into a video clip. The issues raised in the study is not much research on the production of a video clip discusses the multiplex, so the lack of a reference sample for the study multiplex. The goal for the Produce video clips multiplex song "Semalam di Cianjur" based multimedia. The benefits of research to obtain additional material for the song karaoke box and the object of research at the University of Surakarta and give a variant repertoire multiplex video Production for the University of SurakartaThe research methodology used is literature, Observation, Interview, Design, Implementation and Documentation. Formulation of the production steps multiplex video clip consists of the Pre-Production, Production and Post Production. Production multiplex video clip "Semalam di Cianjur" based multimedia is expected to be an inspiration as well as a reference to produce video clips multiplex.Keywords: multimedia journal Â audio video, multiplex, karaoke, song memoriesAbstrak: Multiplek adalah tipe khusus dari lagu karaoke yang memiliki panduan utama vokal, yang membantu Â untuk belajar trek. Vokal tersebut dicatat hanya pada satu sisi dari saluran stereo,sehingga memungkinkan untuk diolah dengan perangkat lunak Sony Vegas menjadi sebuah video klip. Masalah yang diangkat dalamÂ  penelitianÂ  adalah belum banyak penelitian yang membahas tentang produksi video klip multiplek,sehingga kurangnya sample penelitian untuk referensi multiplek. Tujuannya untuk Menghasilkan video klip multiplek lagu â€œSemalam di Cianjurâ€ berbasisÂ  multimedia. Manfaat dari penelitian untuk memperoleh tambahan materi lagu untuk karaoke box dan objek penelitian di Universitas Surakarta serta memberikan varian khasanah produksi video multiplek untuk Universitas Surakarta Metodologi penelitian yang digunakan adalah Kepustakaan, Observasi, Wawancara, Perancangan, Implementasi dan Dokumentasi. Perumusan langkah-langkahÂ  produksi video klip multiplek terdiri dari proses Pra Produksi, Produksi, dan Pasca Produksi.Produksi video klip multiplek â€œSemalam di Cianjurâ€ berbasis multimedia diharapkan dapat menjadi inspirasi serta acuan untuk memproduksi video klip multiplek.Kata kunci : Jurnal multimedia, audio video,multiplek ,karaoke, tembang kenangan